State Bar of California Annual Meeting at San Diego Town and Country Hotel - Watkins, Howard::::::::: (1989)
Former State Bar President Samuel Williams receiving State Bar Award; ?, Joel Murillo, Williams, Emma Pendergrass and State Bar President Colin Wied